THE INFLUENCE OF DIGITAL LITERACY CULTURE AND INTEREST IN READING ON SOCIOLOGY LEARNING ACHIEVEMENT - Putri, Laksita Nirmala; Sulistyaniningsih, Endang; Nadeak, Theresia Evy Yulianty; Jepri, Jumadi; Surata, Surata (Universitas Indraprasta PGRI, 2025)
The accelerated progress in information and communication technology has fundamentally altered the frameworks and interpretations of literacy, broadening its dimensions to include complex social constructs. An individual's inherent enthusiasm for reading emerges as a crucial and foundational component in mastering sociological concepts. This study adopts a survey-based approach, utilizing correlational analysis to explore the relationships between various elements. The variables under investigation comprise one dependent variable, learning achievement (Y), alongside two independent variables: digital literacy culture (X1) and intrinsic reading interest (X2). This can be seen from the significance testing of the regression coefficient conducted with the SPSS program, obtained a value of Sig. 0.000 (Sig. 0.05) and Fcount 25.337 which means that there is a positive influence of the independent variables X1 (Digital Literacy Culture) and X2 (Reading Interest) together on the dependent variable Y (Sociology Learning Achievement). It is concluded: 1) There is a significant influence of digital literacy culture and reading interest together on the sociology learning achievement of public high school students in East Jakarta II. This is evidenced by the acquisition of Sig. 0.000 0.05 and Fcount 25.337; 2) There is a significant influence of digital literacy culture on the sociology learning achievement of public high school students in East Jakarta II. This is evidenced by the acquisition of Sig. 0.001 0.05 and tcount 3.428; 3) There is a significant influence of reading interest on the sociology learning achievement of public high school students in East Jakarta II. This is evidenced by the acquisition of Sig. 0.001 0.05 and tcount 3.500.